Estimation of triangular greenness index for unknown PeakWavelength Sensitivity of CMOS-acquired crop images - De Ocampo, Anton Louise P. (Animo Repository, 2019)
© 2019 IEEE. Notable works on the use of the triangular greenness index (TGI) to estimate vegetation fraction of croplands or chlorophyll content of crops, proved that relevant metrics on crop health monitoring can be derived from images at the visible spectrum. However, the performance of the TGI-based metric in crop health monitoring greatly depends on knowledge of wavelength sensitivities of the CMOS sensors used to obtain the RGB images of the crop. This becomes a problem when generic digital cameras are used and the specifications of the CMOS sensors are not available. The proposed method in this study compensates for the lack of information on the peak wavelength sensitivities of generic CMOS sensors by performing a parametric sweep on the proportions of 670nm-, 550nm-, and 480nm-peak wavelengths to derive a TGI equation normalized by the green signal. This allows the use of any available digital cameras even without prior knowledge of the wavelength sensitivity at the visible spectrum of the installed CMOS sensors.